Strategies for improving the quality of the ground coffee product: a case study at SMEs X Malang, Indonesia. Issue 1 (November 2021) - Ikasari, D M; Santoso, I; Julian, T
Abstract: SMEs X is one of the SMEs in Malang City that produces ground coffee. The increasing number of ground coffee producers in Malang City make SMEs X must be able to survive in the competition so that SMEs X needs to improve the quality of ground coffee products. The methods used are Quality Function Deployment (QFD) and Analytical Hierarchy Process (AHP). The results show that five essential attributes for consumers to improve the quality of ground coffee include unique packaging forms, packaging materials that can maintain quality, attractive packaging colours, convenience for consumers to reach sales locations, and convenience for consumers to get products. Strategies that can be used to improve the quality of ground coffee include redesigning the packaging, improving the ground coffee production process, selecting good quality coffee beans, resetting the selling price of the product, increasing marketing effectiveness, and applying for a permit from the national drug and food agency.